TINJAUAN YURIDIS TENTANG PENGAWASAN MASYARAKAT TERHADAP APARATUR SIPIL NEGARA YANG MELAKSANAKAN TUGAS DALAM PRAKTEK - Bayu Sanjaya (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Supervision is an important aspect in the management of the state apparatus in order that all the tasks, functions, and programs run by the government can function properly. Supervision function also affects the performance because the regulatory process to control the implementation of policies that have been set. Therefore, in order apparatus or government official can achieve good performance will require better oversight function anyway. Through a policy of good supervision and guidance, it is expected that the performance of civil servants that are currently considered weak, particularly in the field of control supervision, can be increased its capacity in order to build a more competitive bureaucratic infrastructure. Methods of public scrutiny of the civilian apparatus of the State in East Kalimantan is the Supervision of the ASN in carrying out the public service through implementation of repressive juridical supervision. This repressive judicial oversight consists of (1) monitoring through pure justice, (2) monitoring through moot court and (3) oversight through an independent agency that is Ombudsman.2. Effect of control methods applicable to the performance of the apparatus is a civil country with their level of performance of the Civil Service wherever they work quantitatively and qualitatively influenced by various factors. These factors can be grouped into two main groups namely factor that comes from within man himself and the factors that come from outside of man. Keyword  : Supervision, Apparatus Civil